(untitled) (Medico Legal Update, 2020)
Caesarean delivery will cause mother to experience anxiety. It can cause interference to the physiological processes in the body. This research aims to find effectiveness of classical music therapy on anxiety level of casarean section mother at Syekh Yusuf Regional General Hospital, Gowa district, by using Hamilton Rating Scale (HARS). This research was an experimental research with a pre-experimental design of one group pre-test and post-test design. The sample was 30 caesarean mothers who met the criteria. Based on the results of Wilcoxon rank statistical analysis test, p value = 0,000 and smaller than the ? value determined at 0.05. Therefore, it can be concluded that classical music therapy is effective to reduce anxiety level of caesarean mothers.